Pemberdayaan Petani Padi di Desa Mas, Ubud, Bali Melalui Pelatihan Pembuatan Lulur Tradisional Berbahan Dasar Beras - A A Sagung Mirah Padmadewi; Luh Putu Mahyuni (Universitas Lancang Kuning, 2021)
Rice farmers roles are very significant in establishing national food security. However, due to weather that is often uncontrolled, affecting the quantity and quality of the harvest, the welfare of rice farmers is still difficult to improve. As an effort to improve the welfare of rice farmers, this community outreach activity seeks to assist farmers, especially in Mas Village - Ubud, increase the added value of their harvests by providing training on making beauty scrubs made from rice and turmeric. The training covers not only the production process, but also packaging and labeling methods. Exploration of potentials and problems was done through the process of observation and interviews. Then the planning process of training activities, training implementation, and evaluation process was carried out, to achieve the goals of community outreach activities. This community outreach activity provides new knowledge and skills for rice farmers and their families in processing rice into traditional scrubs. These new skills are expected to be able to help improve the welfare of rice farmers in Mas Village, especially during this pandemic. This community outreach activity paper contributes to the literature, by offering insight into how the welfare of rice farmers could be improved by providing trainings to increase the added value of agricultural production. In addition, the findings of this community outreach activity can also be applied to different contexts, so that this paper also offers significant practical contribution.